Quantification of the Mechanized Ballast Cleaning Process Efficiency Using GPR Technology - Borkovcová, Anna; Borecký, Vladislav; Artagan, Salih Serkan; Ševčík, Filip (MDPI, 2021)
Ground Penetrating Radar (GPR) has been used recently for diagnostics of the railway infrastructure, particularly the ballast layer. To overcome ballast fouling, mechanized ballast cleaning process, which increases track occupancy time and cost, is usually used. Hence it is of crucial significance to identify at which stage of track ballast life cycle, and level of fouling, ballast cleaning should be initiated. In the present study, a series of in situ GPR surveys on selected railway track sections in Czechia was performed to obtain railway granite ballast relative dielectric permittivity (RDP) values in several phases of railway track lifecycle. GPR data were collected in the form of B-scan, and time-domain analysis was used for post-processing. The results indicate (i) change of railway ballast RDP in time (long term); (ii) a dependency of ballast fouling level on RDP; and (iii) the RDP change during the ballast cleaning process, thus its efficiency. This research aimed to provide new perspectives into the decision-making process in initiating the mechanized ballast cleaning intervention based on the GPR-measured data.
Keywords: ground penetrating radar (GPR); relative dielectric permittivity (RDP); railway ballast fouling; granite ballast; mechanized ballast cleaning; railway infrastructure